2009
DOI: 10.1177/0269215508095087
|View full text |Cite
|
Sign up to set email alerts
|

Predicting accidental falls in people with multiple sclerosis — a longitudinal study

Abstract: In clinical practice, looking at the use of walking aids, investigating proprioception and spasticity, rating Expanded Disability Status Score and using Berg Balance Scale or Timed Up and Go cognitive all contribute when identifying fallers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
317
7
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(350 citation statements)
references
References 34 publications
19
317
7
7
Order By: Relevance
“…The proportions of fallers and injurious fallers found in this study, 58% and 44%, respectively, for the entire sample are consistent with other studies of falls in people with MS. [1][2][3][4]7,11,[22][23][24][25] However, the US sample fell more (72% fallers) than has been found in previous studies and more than the Australian sample, despite on average being less disabled and younger than the Australian sample. The reasons for this difference are uncertain but may be related to younger age, which has been found to be associated with increased fall risk in MS, 26 or to other unmeasured differences in the samples or in health-care delivery between countries.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of fallers and injurious fallers found in this study, 58% and 44%, respectively, for the entire sample are consistent with other studies of falls in people with MS. [1][2][3][4]7,11,[22][23][24][25] However, the US sample fell more (72% fallers) than has been found in previous studies and more than the Australian sample, despite on average being less disabled and younger than the Australian sample. The reasons for this difference are uncertain but may be related to younger age, which has been found to be associated with increased fall risk in MS, 26 or to other unmeasured differences in the samples or in health-care delivery between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research indicates that people with MS fall frequently [4][5][6], likely more than the general population [7][8][9], and more than the elderly, a group in which fall risk [10][11] and its effects are well studied and characterized [12][13][14][15][16][17][18]. A few studies have attempted to ascertain how often people with MS fall, but no comparisons with other groups have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another larger cross-sectional study of falls among people with MS aged 45 to 90 years in the United States (n = 1,089) found that 52 percent of subjects reported falling at least once in the previous 6 months [5]. Most recently, the first prospective study of falls among people with MS found that 63 percent of the subjects (48/76) recorded at least one fall and 58 percent (44/76) recorded two or more falls over a 3 month period [6]. Research on the frequency of falls in people with MS has drawn attention to this important issue but has been limited by crosssectional design, selection and recall bias, and small sample size, as well as a lack of comparison groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations